2018
DOI: 10.15406/ijh.2018.02.00062
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends of rainfall, precipitation and discharges over zambezi river basin, southern africa: review

Abstract: Variability and trends of rainfall, precipitation and discharges over zambezi river basin, southern africa: review Submit Manuscript | http://medcraveonline.com IntroductionHuman influence on the climate system is clear, and recent anthropogenic emissions of greenhouse gases are the highest in history. Their effects, together with those of other anthropogenic drivers, have been detected throughout the climate system and are extremely likely to have been the dominant cause of the observed warming since the mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The results for the RCP 4.5 scenario may also be comparable to a previous study on median change in rainfall that projected to be close to no change in the ZRB for both RCP 4.5 and RCP 8.5 climate scenarios [17]. Further previous studies in the ZRB generally predicted rising temperatures and precipitation decrease and that season may become shorter and more variable, predicting more extended drought periods and more severe floods [43]. The results under RCP 4.5 also agree with previous climate change impact studies that used five GCM (CGCM3.1, CSIRO3.0, ECHAM5, CCSM3.0 and HACDM3), and concluded that the ZRB will have increased temperatures and decreased precipitation leading to reduced streamflow according to a special report on emission scenario A1B (SRES A1B) [18].…”
Section: Swat Simulation High Uncertainty and Strong Consensussupporting
confidence: 84%
See 2 more Smart Citations
“…The results for the RCP 4.5 scenario may also be comparable to a previous study on median change in rainfall that projected to be close to no change in the ZRB for both RCP 4.5 and RCP 8.5 climate scenarios [17]. Further previous studies in the ZRB generally predicted rising temperatures and precipitation decrease and that season may become shorter and more variable, predicting more extended drought periods and more severe floods [43]. The results under RCP 4.5 also agree with previous climate change impact studies that used five GCM (CGCM3.1, CSIRO3.0, ECHAM5, CCSM3.0 and HACDM3), and concluded that the ZRB will have increased temperatures and decreased precipitation leading to reduced streamflow according to a special report on emission scenario A1B (SRES A1B) [18].…”
Section: Swat Simulation High Uncertainty and Strong Consensussupporting
confidence: 84%
“…The GCM, Access1-0 under RCP 8.5 had simulated higher magnitudes of streamflow compared to the other five GCMs, indicating uncertainties, and a conclusion was made based on strong consensus and high uncertainty. The streamflow results for RCP 8.5 showed uncertainty in magnitude, which was also observed by other researchers who stated that there is uncertainty in magnitude and direction of change in the Zambezi River basin response to future GCM projections [43,44]. It was pointed out that GCM runs performed under RCP 8.5 result in more uncertainty than under RCP 4.5 because of climate distribution [17].…”
Section: Main Limitations Of the Studysupporting
confidence: 72%
See 1 more Smart Citation
“…Using data from 138 South African stations between 1910 and 2004, Kruger (2006) detected no significant changes in rainfall in a majority of the stations. Banze et al (2018), from a review of rainfall trends in southern Africa, concluded that rainfall will both increase and decrease in the different parts of the region; however, there is still no total agreement among researchers on the magnitude of the anticipated rainfall change in the region. In contrast, Murungweni et al (2020), from a local-scale study in Limpopo (South Africa), established that there is a non-significant decrease in the annual rainfall.…”
Section: Rainfall Pattern and Trendsmentioning
confidence: 99%
“…Climate change has a significant impact on society primarily through water-related effects, for instance, by affecting sectors such as energy, agriculture, infrastructure, and transport (IPCC 2014a). Hence, besides being an important environmental concern climate change is equally a development limitation particularly in underdeveloped nations (Banze et al 2018;MacAlister & Subramanyam 2018). Meanwhile, the key determinants of current and future climate change impacts on freshwater supplies are rising temperatures, local rainfall variability, and shifts in the magnitude of these variables (IPCC 2014a).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%